2016
DOI: 10.3390/rs8040298
|View full text |Cite
|
Sign up to set email alerts
|

Observing Volcanoes from the Seafloor in the Central Mediterranean Area

Abstract: Abstract:The three volcanoes that are the object of this paper show different types of activity that are representative of the large variety of volcanism present in the Central Mediterranean area. Etna and Stromboli are sub-aerial volcanoes, with significant part of their structure under the sea, while the Marsili Seamount is submerged, and its activity is still open to debate. The study of these volcanoes can benefit from multi-parametric observations from the seafloor. Each volcano was studied with a differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Important results have been obtained during the developments of these mentioned projects, such as the monitoring and study of the Marsili seamount (e.g. Favali et al, 2011;Italiano et al, 2014;Giovanetti et al, 2016), understanding the geolectrical conductivity under some exploring sites of Southern Tyrrhenian Sea (Di Vitale et al, 2009), designing an original tsunami early warning system (Chierici et al, 2012), showing the importance of a multiparameteric geophysical, environmental and oceanographic monitoring (e.g. Monna et al, 2014), to mention just some of the found results.…”
Section: European Multidisciplinary Seafloor and Water Column Observa...mentioning
confidence: 99%
“…Important results have been obtained during the developments of these mentioned projects, such as the monitoring and study of the Marsili seamount (e.g. Favali et al, 2011;Italiano et al, 2014;Giovanetti et al, 2016), understanding the geolectrical conductivity under some exploring sites of Southern Tyrrhenian Sea (Di Vitale et al, 2009), designing an original tsunami early warning system (Chierici et al, 2012), showing the importance of a multiparameteric geophysical, environmental and oceanographic monitoring (e.g. Monna et al, 2014), to mention just some of the found results.…”
Section: European Multidisciplinary Seafloor and Water Column Observa...mentioning
confidence: 99%
“…The TDA has been installed and has successfully operated onboard the stand‐alone GEOSTAR multidisciplinary abyssal observatory (GEophysical and Oceanographic STation for Abyssal Research) during two missions in the Gulf of Cadiz at a depth of about 3200 m from July 2007 to August 2008 and from November 2009 to July 2010 (http://www.moist.it/sites/iberian_margin/1) as a task of the EC NEAREST project and of the EC ESONET‐NoE (European Seas Observatory NETwork‐of Excellence). The TDA has been also installed and tested using the NEMO‐SN1 cabled abyssal observatory (NEutrino Mediterranean Observatory‐ Submarine Network 1) offshore near Catania (Eastern Sicily), at a depth of about 2100 m during a mission from June 2012 to June 2013 [ Chierici et al ., ; Favali et al ., ; Monna et al ., ; Giovanetti et al ., ]. The Gulf of Cadiz and the Western Ionian are nodes of the EMSO research infrastructure (European Multidisciplinary Seafloor and water‐column Observatory, http://www.emso-eu.org).…”
Section: Introductionmentioning
confidence: 99%